An algorithm for rapid flood inundation mapping from optical data using a reflectance differencing technique - Amarnath, Giriraj (Wiley, 2014)
This paper presents an algorithm for flood inundation mapping in the context of emergency response. Rapid satellite-based flood inundation mapping and delivery of flood inundation maps during a flood event can provide crucial information for decision-makers to put relief measures in place.With the development of remote sensing techniques, flood mapping for large areas can be done easily. The algorithm discussed here involves the use of shortwave infrared, near-infrared and green spectral bands to develop a suitable band rationing technique for detecting surface water changes. This technique is referred to as Normalized Difference Surface Water Index (NDSWI). The NDSWI-based approach produces the best results for mapping of flood-inundated areas when verified with actual satellite data. Analysis of results reveals that NDSWI has the potential to detect floodwater turbidity, which was verified using principal component analysis. The application of the technique is informative about flood damages, which are illustrated using the floods in Pakistan in 2010 as an example.